Techniques for delivery of arachidonic acid to Pacific oyster, Crassostrea gigas, spat - Séguineau, Catherine; Soudant, Philippe; Moal, Jeanne; Delaporte, Maryse; Miner, Philippe; Quéré, Claudie (Lipids, 2005)
International audience The present study tested two techniques for dietary supplementation of Crassostrea gigas spat with PUFA, such as arachidonic acid (AA). The first technique consisted of a preliminary enrichment and growth of an algal concentrate (T-ISO, Isochrysis sp.) with AA dissolved in an ethanol solution, the whole culture then being fed to the spat. This enrichment increased the AA weight percentage in T-ISO neutral and polar lipids from 0.6 to 22.4% and from 0.4 to 6.8%, respectively. The second delivery technique was direct addition separately of free AA dissolved in ethanol solution and algal concentrate (T-ISO + AA) to the spat-rearing tank. To test the efficiency of these delivery techniques, oyster spat were supplemented with AA-enriched T-ISO, T-ISO + AA, and T-ISO alone. The possible biological impacts of these dietary treatments were assessed by measuring growth, condition index, and TAG content of oyster spat. Dry weight and condition index of spat fed AA-enriched T-ISO decreased by 24 and 49%, respectively, after 26 d of feeding; basically, TAG content declined 88% after 34 d of conditioning. When AA was added directly to seawater, spat growth and condition index were comparable with those of oysters fed T-ISO alone. AA incorporation in oyster tissues was assessed by analysis of the FA compositions in both neutral and polar lipid fractions. After 34 cl, AA content in neutral lipids reached 7 and 11.7% in the spat fed, respectively, AA-enriched T-ISO and T-ISO + AA, as compared with 1.1% in spat fed only T-ISO. AA incorporation was greater in polar lipids than in neutral lipids, reaching 7.8 and 12.5% in spat fed AA-enriched T-ISO and T-ISO + AA, respectively. A direct addition of PUFA along with the food supply represents an effective and promising means to supplement PUFA to oyster spat.